2013
DOI: 10.1021/jm401407w
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of the Tadalafil Diastereoisomers: A Critical Assessment of Vibrational Circular Dichroism, Electronic Circular Dichroism, and Optical Rotatory Dispersion

Abstract: The stereochemistry of all four stereoisomers of tadalafil is determined using vibrational circular dichroism (VCD), electronic circular dichroism (ECD), and optical rotatory dispersion (ORD) spectroscopy. By comparing experimentally obtained VCD spectra to computationally simulated ones, the absolute configuration of the enantiomeric pair (6R, 12aR)/(6S, 12aS) can be confidently assigned without prior knowledge of their relative stereochemistry. IR and NMR spectra are used to aid the assignment of the relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 68 publications
1
41
0
2
Order By: Relevance
“…In the field of configurational analysis it is very important to use structural information since only then a reliable assignment of the absolute configuration of new molecules is possible [1,2]. Despite enormous progress in instrumentation and methods [3] structural analysis is still a challenge, illustrated by the review of Nicolaou and Snyder [4] who presented data based on which roughly 1000 articles published between 1990 and 2004 have to be revised because of structural reasons.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of configurational analysis it is very important to use structural information since only then a reliable assignment of the absolute configuration of new molecules is possible [1,2]. Despite enormous progress in instrumentation and methods [3] structural analysis is still a challenge, illustrated by the review of Nicolaou and Snyder [4] who presented data based on which roughly 1000 articles published between 1990 and 2004 have to be revised because of structural reasons.…”
Section: Introductionmentioning
confidence: 99%
“…[7] It is mostly used to assign absolute configurations of natural products, [8] pharmaceuticals, [9] and other chiral molecules including products of catalytic asymmetric reactions. [10] However,V CD spectroscopy is not only sensitive to the chirality of am olecule but also to conformational changes, [11] self-aggregation, [12] and intermolecular interactions with solvents.…”
mentioning
confidence: 99%
“…In the near IR region, the experimental ECD (electronic circular dichroism) spectra of endoborneol enantiomers more successfully matched with calculations if equal populations of the three OH rotamers are assumed, in contrast to the energy calculation which indicates one predominant (51.5%) conformer [22]. In a recent study, Qiu et al [23] investigated the tadalafil isomers by chiroptical and NMR methods. The authors showed that the population mixes differ if different levels of theory are used for energy calculations.…”
Section: Structural Analysis Of the Menthol-type Isomersmentioning
confidence: 88%